Impact of atrial arrhythmias on outcome in adults with congenital heart disease. (1st December 2017) - Yang, H.; Kuijpers, J.M.; de Groot, J.R.; Konings, T.C.; van Dijk, A.; Sieswerda, G.Tj.; Post, M.C.; Mulder, B.J.M.; Bouma, B.J.
Abstract: Background: Adults with congenital heart disease (ACHD) are affected by atrial arrhythmias (AA). To elucidate the impact of AA on prognosis, we aimed to determine the impact of AA on death, heart failure and stroke in ACHD patients in a prospective nationwide clinical registry. Methods: All patients aged ≥ 18 years included in the CONCOR registry per October 1st 2015 were analysed. Prior AA was defined as atrial fibrillation, atrial flutter or unspecified AA before inclusion in CONCOR and new-onset AA as a first documented AA during follow-up. The outcomes were death, first stroke and first admission for heart failure (HF). Results: The study cohort comprised 14, 224 patients (baseline median age 33.6 [IQR 23–47], male 49.5%, AA n = 1501, complex defect 10.3%, repaired defect 58.9%). Median follow-up was 6.5 years [IQR 3–10]. Adjusting for age, sex, repair status and defect severity, patients with prior AA had higher mortality and more HF admissions, but no increased risk of stroke compared to those without AA (HR = 2.11; 95% CI = 1.79–2.49; p < 0.001, HR = 4.06; 95% CI = 2.66–6.19; p < 0.001 and HR = 1.09; 95% CI = 0.71–1.68; p = 0.698, respectively). New-onset AA during follow-up was significantly associated with stroke (HR = 2.04; 95% CI = 1.05–3.96; p = 0.036). Conclusions: ACHD patients with prior AA have a 2-fold increased risk of death and a 4-fold increased risk of heart failure, but no increased risk for stroke compared to those without AA. Defect severity and age appear to be more important risk factors for stroke than prior AA. Stroke risk is increased only after conversion of new onset AA. Highlights: ACHD with atrial arrhythmias are at increased risk for death and heart failure. Atrial arrhythmia was not significantly associated with risk of stroke in ACHD. Age and defect severity are important risk factors for stroke in ACHD patients. Stroke prevention remains crucial, especially in older patients with complex defect.